Video Games and Aesthetic Contemplation. Issue 5 (July 2021) - Atkinson, Paul; Parsayi, Farzad
Video games present incredibly rich visual environments that can be studied from a variety of perspectives including those germane to the visual arts. The medium has evolved to such a degree that evaluation should not rest on whether an individual game can be considered art, but what types of aesthetic engagement the medium affords. A key figure in the study of the visual arts is aesthetic contemplation, in which extended attention reveals aesthetic differences. Although the video game presents many sites and scenes worthy of such contemplation, this mode of spectatorship requires sufficient time and space to attend to a visual object. In order to open up a space for aesthetic engagement, many of the ludological and narrative demands of the game must recede. In this article, we will investigate the degree to which players have choice in how, or how long, they attend to a game's visual environment.